Changes in the upper airway and its surrounding structures after bimaxillary surgery in patients with cleft-related Class III deformity - Ho, Chung-Yi; Lu, Ting-Chen; Hsieh, Yuh-Jia; Chang, Chun-Shin; Chen, Ying-An; Liao, Yu-Fang (The Angle orthodontist, 2024)
To compare upper airway changes following bimaxillary surgery for correction of Class III deformity between patients with unilateral cleft lip and palate (UCLP) and bilateral cleft lip and palate (BCLP) and to compare the preoperative and postoperative upper airway among patients with UCLP and BCLP to healthy controls. Sixty adults with CLP-related skeletal Class III deformity (30 UCLP and 30 BCLP) who consecutively underwent bimaxillary surgery were studied retrospectively. Cone-beam computed tomography (CBCT) was performed before and after surgery to measure upper airway and movements of facial skeletal and surrounding structures. CBCT images from 30 noncleft skeletal Class I adults, matched by age, gender, and body mass index and without surgical intervention, served as controls. After surgery, the volume of the nasopharynx increased in patients with CLP (both P < .001). Patients with CLP did not differ from controls in postoperative volume of the nasopharynx or oropharynx. However, the nasal cavity differed significantly between patients with CLP and controls (P < .001). After bimaxillary surgery, the nasal cavity of patients with CLP differed significantly compared with the controls. Volumes of the nasopharynx and oropharynx did not differ between patients with CLP after surgery and controls.